(untitled) (Global Journal of Medical Research, 2024)
Hypernatremia a rare condition in newborns is marked by elevated plasma sodium levels exceeding 150 mEq L It is more common in newborns who are exclusively breastfed or with excessive weight loss Hypernatremic dehydration HD presents severe risks including cerebral edema and other neurological complications A female newborn 12 days old birth weight 2800g was brought to the Emergency Department due to a 30 decrease in birth weight and reduced urine output The newborn was solely breastfed every 2 hours with a good notion of adequate reflexes and tolerance Physical examination revealed a skeletal appearance jaundice sunken eyes and skin turgor Blood pressure measurement was unsuccessful while capillary blood glucose was 96g dL A saline bolus 10 mL Kg was administered Venous blood gas analysis showed pH 7 39 lactate 4 3 mmol L HCO3- 21 8 mmol L and Na 180 mEq L